LSPR's Social Media Narrative in Maintaining the Legitimacy of Formal Education: A Critical Discourse Analysis of LSPR's Digital Communication Strategy - Ivanaldy Kabul; Rudy Harjanto; Geofakta Razali (Yayasan Ilomata, 2026)
This study examines how LSPR Institute of Communication & Business constructs the legitimacy of formal education through its social media discourse. Amid increasing competition and state regulation of educational quality, private higher education institutions must strategically negotiate public perception. This research applies Critical Discourse Analysis to analyze three pinned Instagram posts from @lsprjakarta and triangulates the findings through in-depth interviews with nine informants consisting of students, parents, lectures, and staff. The textual analysis reveals the use of affective-inspirational language emphasizing family-oriented diction to frame educational achievement as collective belonging. The discursive. practice analysis shows collaborative content production and distribution that reinforces institutional integration and network expansion. The social practice analysis demonstrates that LSPR constructs formal education legitimacy through symbolic positioning as a